"All of these things interact, that's why it's such a wicked problem": Stakeholders' perspectives of what hinders low back pain care in Australia and how to improve it - Nathalia Costa; Carmen Huckel Schneider; Anita Amorim; Sarika Parambath; Fiona Blyth (BMC, 2024)
Abstract Background Low-quality care for low back pain (LBP) is pervasive in Australia. Drivers of low-quality care have been identified elsewhere and include misconceptions about LBP, vested interests and limited funding for evidence-based interventions. Yet, the literature that identified such drivers is not specific to the Australian context, and therefore, it is likely to represent only part of the local problem. This study aimed to determine where the most influential drivers of LBP care are in the Australian healthcare system and what could be done to address them. Methods Clinical leaders from various disciplines, academics, hospital managers, policy-makers, consumers involved in LBP advocacy, board members of relevant health profession boards and private insurers were invited to participate in one-on-one interviews. Interviews were transcribed verbatim. Interview data were analysed using content analysis. Results We interviewed 37 stakeholders. Challenges that hinder LBP care in Australia included variability in care and inconsistent messages, funding models that are not supportive of appropriate care for LBP, the community's understanding of LBP, vested interests and commercial forces, difficulties in accessing timely and affordable conservative care, neglect of social determinants and health inequities, short consultations, siloed practices, uncertainties that stem from gaps in evidence and the experience of having LBP, individual and contextual variability, the mismatch between evidence and practice, the Australian healthcare system itself, the lack of political will and acknowledgement of LBP as a public health issue, stigma, the need to improve human aspects and the compensation system. When discussing factors that could improve LBP care, participants raised collaboration, changes in funding, improvement of access to - and affordability of - models of care and care pathways, public health campaigns targeting LBP, enhancement of policy and governance, increasing and better training the workforce, consideration of inequities, making improvements in information sharing and reforming the worker's compensation sector. Conclusions LBP is a wicked problem, influenced by several systemic factors. An agenda for system change in the LBP landscape should be guided by a collaborative, coherent and integrated approach across sectors to enhance quality of care and system efficiency for those who seek and provide care.